Analysis Of Thrust Density Calculation For Linear Dc Actuators - Awaludin, Noor Azita (2006)

(untitled)
In recent years, researcher has developed many actuators with different configurations depending on application required. Linear actuator has become one of the most popular actuator used in industry especially in factory automation. Linear motor, which have a compact and simple structure are easy to control compare to rotational motor [1]. The advantages of linear actuator are small size, low power and high thrust. The thrust of linear motor can be applied on to the load without any mechanical loss as rotation motor. But then, the generation of thrust produced by linear actuators is barely being fully investigated. Therefore, problem arises in producing low cost machine but with higher thrust production. A study was conducted with the objective to investigate thrust density characteristics in relation with dimension. Two designs were tested, that is Linear DC actuator using electromagnetic application and Linear DC actuator which using permanent magnet application. The range of current supplied to wound coil is 1 A to 3 A, while permanent magnet produced magnetic flux directly. Expressions on the thrust generation on both linear actuators were derived in relation with the dimension and size of the machine. Derivation was done based on a few assumptions that may constitute to the objectives of this study. For clarification purposes, experiment on both linear actuators was done depending on the physical condition. Through the experimental result, comparison can be made between theoretical and experimental result in order to find the thrust density characteristic of linear actuator. Basically, the objective of this study is achieved when comparison that has been made for both type of linear actuator shows the largest error was only 20%. For future improvement, a few prototype of linear actuator with different configuration of closed loop path for the flux to flow can be made. This study only concentrated on the same closed loop path of flux flows with a few assumption have to be taken which are the temperature and type of material for yoke is neglected. It is important to take the a few assumptions in order to focus on the thrust density characteristics in relation with the dimension.